2021
DOI: 10.1039/d1gc00603g
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing polarity and viscosity to identify green binary solvent mixtures as viable alternatives to DMF in solid-phase peptide synthesis

Abstract: Solid-phase peptide synthesis (SPPS) enables routine synthesis of virtually any type of peptide sequence and is the preferred method for peptide synthesis in academia and the pharmaceutical industry alike. Still,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 58 publications
(93 reference statements)
1
63
0
Order By: Relevance
“…Fine-tuning the chemical/physical features of solvents by using a binary mixture is a valuable instrument for obtaining the appropriate polarity and/or viscosity for successful resin swelling and reagent solubilization, 81 as highlighted in the guidelines for a perfect SPPS solvent. 46 The influence of different solvent mixtures on swelling was first described by the North group, who developed a computational model outlining, for the first time, that resin swelling did not correlate linearly with solvent composition. More importantly, they showed that a binary mixture could be better at achieving swelling than neat solvents; mimicking the properties of traditional, polar, aprotic solvents; and replacing them.…”
Section: Technologies and Synthesis Modifications Toward “Greening” Peptide Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Fine-tuning the chemical/physical features of solvents by using a binary mixture is a valuable instrument for obtaining the appropriate polarity and/or viscosity for successful resin swelling and reagent solubilization, 81 as highlighted in the guidelines for a perfect SPPS solvent. 46 The influence of different solvent mixtures on swelling was first described by the North group, who developed a computational model outlining, for the first time, that resin swelling did not correlate linearly with solvent composition. More importantly, they showed that a binary mixture could be better at achieving swelling than neat solvents; mimicking the properties of traditional, polar, aprotic solvents; and replacing them.…”
Section: Technologies and Synthesis Modifications Toward “Greening” Peptide Synthesismentioning
confidence: 99%
“…Considering all aspects, 3 : 7 DMSO/DOL (Table 3, entries 38–42) and 3 : 7 DMSO/2-MeTHF (Table 3, entries 33–37) provided the best results when compared to DMF, while 4 : 6 NBP/DOL gave slightly worse results (Table 3, entry 43). 46…”
Section: Technologies and Synthesis Modifications Toward “Greening” Peptide Synthesismentioning
confidence: 99%
“…Alternatively, natural deep eutectic solvents (NADES) have also been applied [12,[20][21][22][23][24][25][26] for this purpose. In general, many multicomponent liquid mixtures, such as NADES [27][28][29][30][31][32], ionic liquids [30,[33][34][35], and organic solvent mixtures [36][37][38] are considered as promising green solvents. Another reason for binary solvents research is the optimization of reactants concentrations and crystallization efficiency [39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…The typical aqueous SPPS resins PEGA [39] and ChemMatrix [40] are not well suited for large‐scale peptide synthesis due to their high cost and excessive swelling in trifluoroacetic acid (TFA), [28b] and we thus examined the more common polystyrene (PS)‐based resins [41] instead. Although several studies on resin swelling in different solvents were reported, [27c,28c,d,42] to our knowledge swelling in mixtures of water with green DA solvents was not evaluated.…”
Section: Methodsmentioning
confidence: 99%